Development of a Versatile Nanostructured Lipid Carrier (NLC) Using Design of Experiments (DoE)-Part II: Incorporation and Stability of Butamben with Different Surfactants - Ananda P. Matarazzo; Carlos A. Rios; Gabriela Gerônimo; Roberta Ondei; Eneida de Paula; Márcia C. Breitkreitz (MDPI AG, 2024)
Nanostructured lipid carriers (NLCs) are typically composed of liquid lipids, solid lipids, and surfactants, enabling the encapsulation of lipophilic drugs. Butamben is a Class II anesthetic drug, according to the Biopharmaceutical Classification System (BCS); it has a log P of 2.87 and is considered a 'brick dust' (poorly water-soluble and poorly lipid-soluble) drug. This characteristic poses a challenge for the development of NLCs, as they are not soluble in the liquid lipid present in the NLC core. In a previous study, we developed an NLC core consisting of a solid lipid (CrodamolTM CP), a lipophilic liquid with medium polarity (SRTM Lauryl lactate), and a hydrophilic excipient (SRTM DMI) that allowed the solubilization of 'brick dust' types of drugs, including butamben. In this study, starting from the NLC core formulation previously developed we carried out an optimization of the surfactant system and evaluated their performance in aqueous medium. Three different surfactants (CrodasolTM HS HP, SynperonicTM PE/F68, and CroduretTM 40) were studied and, for each of them, a 23 factorial design was stablished, with total lipids, % surfactant, and sonication time (min) as the input variables and particle size (nm), polydispersity index (PDI), and zeta potential (mV) as the response variables. Stable NLCs were obtained using CrodasolTM HS HP and SynperonicTM PE/F68 as surfactants. Through a comparison between NLCs developed with and without SRTM DMI, it was observed that besides helping the solubilization of butamben in the NLC core, this excipient helped in stabilizing the system and decreasing particle size. NLCs containing CrodasolTM HS HP and SynperonicTM PE/F68 presented particle size values in the nanometric scale, PDI values lower than 0.3, and zeta potentials above |10|mV. Concerning NLCs' stability, SBTB-NLC with SynperonicTM PE/F68 and butamben demonstrated stability over a 3-month period in aqueous medium. The remaining NLCs showed phase separation or precipitation during the 3-month analysis. Nevertheless, these formulations could be freeze-dried after preparation, which would avoid precipitation in an aqueous medium.